Renewable energy implementation and use in German regions. Contributions to regional energy transitions strategies considering context, time and practice. Implementierung und Nutzung von erneuerbaren Energien in deutschen Regionen. Beiträge zu regionalen Energiewendestrategien unter besonderer Berücksichtigung von Kontext, Zeit und Praxis. - Lutz, Lotte Marie (My University, 2019)
Mit einer empirischen, räumlich differenzierten Analyse der naturräumlichen und sozio-ökonomischen Kontextbedingungen für die Nutzung erneuerbarer Energie in allen deutschen Landkreisen identifiziert die Arbeit neun Typen von Regionen, die energy context types. In einem energy context type befragt sie Akteure aus der regionalen Administration zu ihren praktischen Erfahrungen mit der Implementierung von erneuerbaren Energien. Als erfolgsversprechend haben sich eindeutige politische und wirtschaftliche Rahmenbedingungen herausgestellt, sowie Prozessmanagement, der Austausch mit ExpertInnen und MitarbeiterInnen anderer Regionen sowie eine breit aufgestellte Finanzierung aus mehreren Quellen. Ergänzend zu den empirischen Untersuchungen präsentiert der Autor in der Arbeit konzeptionelle Themen zur zeitlichen Dynamik von Transformationsprozessen: der time-intransformations-approach ermöglicht es, zeitliche Dynamiken konkreter in Begleitung und Management von Transformationsprozessen berücksichtigen zu können. Es wird ein Kompromiss vorgestellt, der einerseits eine effiziente Entwicklung von regionalen Energiewendestrategien ermöglicht, anderseits aber auch die Individualität der Regionen berücksichtigt. Für jeden der neun energy context types können generische regionale Energiewendestrategien entwickelt werden, die auch die Erfahrungen aus der Praxis sowie zeitliche Dynamiken von Transformationsprozessen berücksichtigen. Transdisziplinäre Forschung ist ein erfolgversprechender Ansatz, um vielen Herausforderungen der Energiewende zu begegnen.

The present work contributes to the understanding of transition processes towards a sustainable use of regional renewable energy by focusing on the role of contextual conditions, practical experiences, and temporal dynamics in the implementation and use of renewable energy in German regions. In this way, this work wants to contribute fostering the development of regional energy transition strategies for the realization of the Energiewende. The conceptual background for this piece of transformation research lies in three bodies of literature dealing respectively with transitions of socio-technical systems, transformations of socioecological systems, and time ecology. From a critical engagement with this literature, three main results have emerged. First, an evidence-based, spatially distinct analysis of contextual conditions for the use of renewable energy in all German regions has resulted in the identification of nine types of regions, so-called energy context types. Second, empirical research on practices in regional settings learned from the knowhow of actors from regional administration has shown that political and economic conditions are crucial as well as that process management, exchange, and learning are helpful for renewable energy implementation. Third, conceptual work about a deeper understanding of the temporal dimensions of transformation processes has made it possible to point out a three-step approach to include temporal dynamics into sustainability transformations management - the time-in-transformations-approach. The literature suggests that regions need to be treated individually; but developing an energy transition strategy for each region individually would be extremely resource intensive. Overall, my work outlines a compromise for a more efficient approach towards regional energy transition strategies which still considers the individuality of regions. As a result, suggest to develop generic regional energy transition strategies that are adapted to each of the nine energy context types of German regions, that include the experiences of practitioners, and that consider temporal dynamics of transformation processes. Transdisciplinary research is a promising approach to meet many of the challenges for the realization of the Energiewende. A transdisciplinary steering board on the national level could create generic regional energy transition strategies that guide the energy transition and give clear goals and orientation for the realization of policies on the lower levels. On the regional level, these strategies would need to be adapted with regard to each region´s situation. Relying on the results of my research, conclude that this could also be informed through transdisciplinary processes.
Keywords: Energie; Erneuerbare Energie; Energiewende; Landkreis; Region; Typologie; Regionale Disparität; Klimaschutz; Rahmenbedingung; Transformation; Strategie; Akteur; Finanzierung; Fallstudie